E-compare : common features of various website genres. - Heng, Lisa Li Shih. (2008)
The report aims to provide guidelines for entities that intend to host company websites, venture into e-commerce, set up web portals or put up information online to create awareness. A web-based content analysis, focusing on Singapore sites, was performed on three types of sites: portals, e-commerce and informational sites.